Studi Komperatif Prinsip Asuransi Jiwa Takaful dan Asuransi Jiwa Konvensional - Ilyas Ilyas (Universitas Syiah Kuala, 2014)
Everyone is aware that the life is full of uncertainty, except the death. The uncertainty causes a risk that is a loss for a person. The risks are sick, accident, death, etc. all will cause suffering and it is circumvented by transferring the risk to insurance hence it is easier for the person. Therefore, there is an agreement between the person worrying the risk and the company taking the responsibility. Nowadays, apart from conventional insurance, there is also Islamic insurance. Islamic insurance, including Takaful Life Insurance, avoids three things banned in Islamic rule namely; uncertainty, gambling, and interests as found in life insurance recently. This research aims to explain a comparative study of life insurance of Takaful and conventional. A Comparative Study on the Life Insurance of Takaful and Conventional